Blockchain Sebagai Solusi Transparansi Dalam Keuangan Syariah - Aini, Fauqah Nuri; J, Julina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Transparency is a fundamental principle in Islamic finance, which upholds the values of justice, honesty, and openness. However, conventional practices of financial reporting in Islamic institutions still face various challenges such as delayed information, data manipulation, and limited public access. This study aims to examine the potential of blockchain technology as a solution to enhance transparency in the Islamic finance ecosystem. Using a qualitative descriptive approach based on literature review, this research analyzes the core characteristics of blockchain—immutability, decentralization, and smart contracts—and their relevance to Sharia principles. The findings indicate that blockchain holds significant potential in improving accountability and efficiency, especially in sectors such as zakat management, waqf, and Islamic microfinance. Case studies of implementations like Blossom Finance and WaqfChain show positive impacts on information transparency and public trust. However, challenges remain in areas such as regulation, Sharia compliance, and technological literacy. Therefore, synergy among regulators, Sharia scholars, financial institutions, and technology providers is crucial to realize a sustainable and Sharia-compliant digital transformation in Islamic economics